2010
DOI: 10.3109/10715762.2010.499906
|View full text |Cite
|
Sign up to set email alerts
|

Does radiotherapy increase oxidative stress? A study with nasopharyngeal cancer patients revealing anomalies in isoprostanes measurements

Abstract: This study aimed to examine if exposure to ionizing radiation during clinical radiotherapy (RT) causes increased oxidative damage. Seven patients with nasopharyngeal cancer (NPC) who underwent RT took part in this controlled-trial study. Blood and urine samples were obtained for F(2)-isoprostanes (F(2)-IsoPs) measurement. Urinary F(2)-IsoPs levels were elevated pre-treatment and remained high (but did not increase) during treatment, but decreased to the normal range after treatment. Plasma F(2)-IsoPs decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding the effect of head and neck radiotherapy on the levels of oxidative/nitrosative stress biomarkers, a study demonstrated that conventional radiotherapy in patients with nasopharyngeal cancer did not increase the urinary and plasma levels of F(2)‐isoprostane (a lipid peroxidation biomarker); on the contrary, the levels decreased . In another study , when patients with head and neck cancer were individualized to radiotherapy alone, no significant change was observed in mean values of plasma MDA levels between the pre‐ and post‐radiotherapy periods.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of head and neck radiotherapy on the levels of oxidative/nitrosative stress biomarkers, a study demonstrated that conventional radiotherapy in patients with nasopharyngeal cancer did not increase the urinary and plasma levels of F(2)‐isoprostane (a lipid peroxidation biomarker); on the contrary, the levels decreased . In another study , when patients with head and neck cancer were individualized to radiotherapy alone, no significant change was observed in mean values of plasma MDA levels between the pre‐ and post‐radiotherapy periods.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the systemic redox balance was maintained in these patients, despite the RT effects. These data, however, require a careful analysis because several studies suggest that radiation increases the oxidative stress in different tissues [11,12]. What it can be stated is that, at least in these patients, the local oxidative stress did not lead to a systemic redox imbalance that could be…”
Section: Systematics Of Data Collectionmentioning
confidence: 95%
“…Cancer cells, compared to normal cells, [181,182] Isoprostanes Breast, nasopharynge [183,184] malondialdehyde (MDA) Colon, oral, breast [185][186][187] Lipid peroxidation 4-hydroxy-2, 3-nonenal (HNE) Liver, thyroid carcinoma [178,179] Protein oxidation carbonyl groups Colon [185] superoxide dismutase (SOD) Prostate [188] glutathione peroxidase 3 (GPX3) Breast, prostate [189,190] Expression levels /activity thioredoxin reductase-1 (TR1) Lung, prostate [191][192][193] are under increased oxidative stress associated with oncogenic transformation, alterations in metabolic activity, and increased generation of ROS [136]. The biological effects of ROS in cancer are multiple and non-linear.…”
Section: Targeting Ros As a Cancer Thera-peutic Strategymentioning
confidence: 99%